Efficacy and safety of fire acupuncture for psoriasis vulgaris: A protocol of systematic review and meta-analysis of randomized clinical trials. Issue 12 (26th March 2021) - Cheng, Xueli; Lai, Jiawen; Zhang, Yuelin; Lin, Liyun; Xu, Donghan; Zhong, Zhenghong; Wu, Qibiao; Liu, Jing
Abstract: Introduction: Fire acupuncture is commonly used for the treatment of psoriasis vulgaris, but the efficacy and safety of fire acupuncture for psoriasis vulgaris remain unclear. Methods: This systematic review and meta-analysis will be conducted and reported strictly according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Five databases including China National Knowledge Infrastructure (CNKI), Wanfang, VIP, Chinese biomedical literature, and Pubmed will be retrieved for potentially eligible studies from their inception to Jan. 2021. All randomized clinical trials comparing fire acupuncture versus no fire acupuncture in the treatment of psoriasis vulgaris will be retrieved and assessed for inclusion. RevMan5.3 software provided by Cochrane collaboration will be used for the analysis. Randomized Clinical Trials Data will be extracted by 2 researchers independently, risk of bias of the meta-analysis will be evaluated based on the Cochrane Handbook for Systematic Reviews of Interventions. The primary endpoint is the total effective rate, the secondary outcomes are the Psoriasis Area Severity Index (PASI) score, the recurrence rate and the adverse reactions. Results: This study will systematically evaluate the efficacy and safety of fire acupuncture for psoriasis vulgaris. The results will be published in a peer-reviewed journal. Conclusion: This systematic review will evaluate the effects of fire acupuncture in patients with psoriasis vulgaris, thus providing evidence to the clinical application of this therapy.